Pengaruh Biaya Produksi terhadap Pendapatan Petani Jagung Desa Benteng Paremba Pinrang (Analisis Ekonomi Islam): The Effect of Production Costs on the Income of Maize Farmers in Benteng Paremba Village Pinrang (Islamic Economic Analysis) - Putri, Winda Reskiyan; Firman; Semaun, Syahriyah (Program Studi Ekonomi Syariah IAIN Parepare, 2023)
This study aims to determine how much Production Costs in Benteng Paremba Pinrang Village, how good the income of corn farmers in Benteng Paremba Pinrang Village, the relationship of Production Costs to the Income of Corn Farmers in Benteng Paremba Pinrang Village, and the Effect of Production Costs on the Income of Corn Farmers in Benteng Paremba Pinrang Village. This research is quantitative research with simple linear regression method. The data sources used are primary data in the form of observation results, interviews, and secondary data including documents and archives of Benteng Paremba village. The method used to test the hypothesis is using one sample t-test, product moment correlation test, heteroscedasticity test, normality test, autocorrelation test, linearity test, and determination test. The amount of costs incurred by corn farmers is IDR 4,870,934. Thus the income of corn farmers in Benteng Paremba Pinrang Village is good in taking production costs because it can be concluded that the income of corn farmers in Benteng Paremba Pinrang Village is in the good category, which is in the classification score of 68.01% - 84.00%. The test value results also found that there is a positive and significant relationship between Production Costs and Corn Farmer Income. Testing the coefficient of determination obtained 13.6% of production costs affect the income of corn farmers it means weak and the remaining 86.4% is influenced by other factors or not discussed in this study.